The Effect of E-Performance Appraisal System and Additional Income of Civil Servant on Performance with Job Satisfaction as Intervening Variable in the Regional Secretarial of Mojokerto City - Widya Windasari (Universitas Airlangga, 2019)
Since 2019 the Government of Mojokerto City has made efforts to convert the performance appraisal system manually into an online system. This effort was made to realize effective and efficient governance based on technology. E-Performance is a website-based application used by the Government of Mojokerto City to manage and assess employee performance. E-Performance is a staffing system that can determine oversight to the activities of civil servants, who can then directly determine the amount of the additional income of civil servant. The purpose of this study is to analyze and prove the effect of e-performance appraisal system and additional income of civil servant on performance in the Regional Secretariat of Mojokerto City with job satisfaction as an intervening variable. This research uses a quantitative approach combined with an explanatory method. The results of this study conclude several things, including: 1.) E-Performance appraisal system has significant positive effect on performance; 2.) Additional income of civil servant has significant positive effect on performance; 3.) E-Performance appraisal system has significant positive effect on job satisfaction; 4.) Additional income of civil servant has significant positive effect on job satisfaction; 5.) Job satisfaction has significant positive effect on performance; 6.) E-Performance appraisal system and additional income of civil servant have significant positive effect on performance through job satisfaction.